1978
DOI: 10.1136/jcp.31.10.944
|View full text |Cite
|
Sign up to set email alerts
|

Further studies on the umbilical cord and its water content.

Abstract: SUMMARY The results show that the varied appearance of the umbilical cord at birth can be related to its water content and that there are associated changes to be seen histologically in all layers of the cord, but especially in Wharton's jelly. Quantimet analysis confirms these findings and highlights a small group where dual pathology may exist. The relationship between oedematous cords, large drip volume, and respiratory distress in the newborn is considered, and a possible explanation for reduced placental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 5 publications
0
13
0
2
Order By: Relevance
“…The appearance of the umbilical cord varies substantially and is mainly due to differences in water content retained by the gelatinous Wharton’s jelly that surrounds the blood vessels (Scott and Wilkinson 1978; Sloper et al 1979). The mean water content decreases with increasing duration of gestation, and the fetal end of the cord has a higher water content than does the placental end (Sloper et al 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The appearance of the umbilical cord varies substantially and is mainly due to differences in water content retained by the gelatinous Wharton’s jelly that surrounds the blood vessels (Scott and Wilkinson 1978; Sloper et al 1979). The mean water content decreases with increasing duration of gestation, and the fetal end of the cord has a higher water content than does the placental end (Sloper et al 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Vessel contractions within the first couple of minutes after birth (Yao and Lind 1974) will determine the blood content of the cord sample. Umbilical cords differ in thickness and overall appearance, largely due to varying amounts of Wharton’s jelly (Scott and Wilkinson 1978), the amount of which decreases with the duration of gestation (Sloper et al 1979). The cord mercury concentration is therefore usually expressed in terms of dry weight (Akagi et al 1998; Dalgård et al 1994).…”
mentioning
confidence: 99%
“…The water content of the umbilical cord has been studied in great detail by Scott and Wilkinson (1978). Edematous cords had a water content of 93.5%, and wrinkled cords had 89.2% water.…”
Section: Cysts and Edemamentioning
confidence: 99%
“…It was suggested that amount of Wharton's jelly or its water content goes on decreasing with advancing gestation. 6 A condition differing from that described here is 'insertion funiculi furcata' in which the site of cord insertion is normal but, prior to insertion, the vessels lose their protective covering of Wharton's jelly. 1 In this entity, the vessels branch before reaching the placental surface.…”
Section: Discussionmentioning
confidence: 54%